Potential and challenges of implementing the metaverse concept in islamic banking: A literature analysis - Khaidar Rahmaini Jamila; Yona Fitri; Iskandar Muda; Andri Soemitra; Yusrizal Yusrizal (Indonesia Auditing Research Journal, 2025)
The rapid development of digital technology has given rise to various disruptive innovations, one of which is the metaverse concept. In the context of the financial industry, the metaverse opens new opportunities for providing more interactive, personalized, and efficient services. This article aims to comprehensively analyze the potential and challenges of implementing the metaverse concept in Islamic banking through a literature review of various scientific publications, industry reports, and other relevant sources that discuss the relationship between metaverse technology and Islamic financial principles. In terms of potential, the metaverse offers various strategic opportunities for Islamic banking, including the development of virtual branches that enable direct interaction between customers and bank employees in real time without geographical limitations, increasing financial literacy through virtual experience-based education, and creating a digital halal ecosystem that aligns with Islamic values. Furthermore, the integration of blockchain technology into the metaverse can support transparency, transaction efficiency, and Sharia compliance through the implementation of smart contracts based on Islamic muamalah principles. However, the implementation of the metaverse in Islamic banking also presents complex challenges. This article concludes that the successful implementation of the metaverse concept in Islamic banking relies heavily on cross-sector collaboration between regulators, industry players, academics, and the Islamic scholar community to develop a framework that encourages innovation while maintaining compliance with Islamic principles. The findings of this study are expected to provide theoretical and practical contributions to the development of sustainable digital transformation strategies for Islamic banking in the era of the Fourth Industrial Revolution and the Fifth Industrial Revolution.